Summary report 1996 : doctorate recipients from United States universities - Henderson, Peter H. (National Academy Press, 1998)
Report 1996 -- Highlights -- Copyright -- PREFACE AND ACKNOWLEDGMENTS -- CONTENTS -- INTRODUCTION -- TRENDS IN DOCTORATE RECIPIENTS -- CONTINUED BUT SLOWING INCREASE IN RESEARCH DOCTORATE AWARDS -- Rate of Growth -- Trends in Baccalaureate, Masterâ€?s, and Doctorate Degrees -- Doctorates per Institution -- FIELD OF DOCTORATE -- Science and Engineering Fields -- Humanities, Education, and Professional Fields -- GENDER -- Gender by Field -- RACE/ETHNICITY -- Race by Field -- CITIZENSHIP -- Country of Citizenship -- Institutions